PERENCANAAN STRATEGI BERDASARKAN ANALISIS MISI, VISI DAN SWOT RS DI BANTUL YOGYAKARTA - Chanif Kurniasari (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2019)
Background: The concept of strategic management has not been optimally yet done by the Bantul Yogyakarta Hospital. The issue of the development and preparation of a strategic plan has been done but is more of an interest in the management of accreditation. In addition, there are several themes that have become the thoughts of the leadership of the Bantul Yogyakarta Hospital, namely the JKN program, there are many hospitals that near of Bantul Yogyakarta Hospital, and increasing number of people around of the Hospital. For this reason, recommendations for strategy formulation are needed.Objective: This study is aimed to develop recommendations for strategy formulation for Hospital with mission evaluation, vision and SWOT analysis.Method: This study used a qualitative method with a type of case study. The speaker in this study is the leader of the Foundation and Hospital.Results: The results of the exploration of mission and vision produce 5 mission points and 5 vision points. Internal environment analysis used Value Chain Model from Porter and external environment analysis used the Health Service System Environmental Analysis Model. The results of the SWOT analysis produced 17 strengths, 15 weaknesses, 6 opportunities and 4 threats. The preparation of the SWOT matrix produced: 5 SO strategies, 2 WO strategies, 2 ST strategies, and 2 WT strategies. Strategic recommendations for Hospital are: goal strategies in the form of recommendations for mission and vision statements, low cost strategies, implementation strategies, penetration strategies, market development strategies and product development strategiesConclusion: Re-formulation of the mission and vision of Hospital based on the results of the exploration of mission and vision. From the results of the mission and vision formulation, internal and external environmental analysis, and SWOT analysis formulated a strategy formulation recommendation, namely the objective strategy in the form of recommendations for mission and vision statements, low cost strategies, implementation strategies, penetration strategies, market development strategies and product development strategies.